Dyspareunia in Puerto Rican Middle-aged Women - Avellanet, Yaniris R. (2009)
Dyspareunia appears to be a common sexual dysfunction. There is a lack of studies that address female sexual dysfunction (FSD) in Puerto Rico. The present cross- sectional study characterized dyspareunia in a sample of Puerto Rican women aged 40–59 years and evaluated the relationship between reported dyspareunia with demographic, lifestyle and health factors. Nine-hundred and twenty Puerto Rican women participated in health fairs conducted in 22 municipalities between May 2000 and November 2001 where they filled out a questionnaire. Contingency table and chi-squarestatistics were used to evaluate the bivariate associations of dyspareunia with demographic, lifestyle and health factors. Crude and multivariate logistic regression model were used to estimate the magnitude of the association between dyspareunia and demographic, lifestyle and health factors. The overall prevalence of dyspareunia in this population was 18%. Dyspareunia was somewhat lower among women aged 40–49 years (17%) than among those aged 50–59 years(21%), not reaching statistical significance. Dyspareunia was associated to educational attainment, employment status, menopausal status, current hormone therapy use, genitourinary symptoms, and loss of libido (p < 0.05). Current cigarette smoking, body mass index, physical activity, alcohol use, parity, and ever use of oral contraceptives were not associated with dyspareunia in bivariate analysis (p>0.05). In the multivariate analysis, incontinence (POR=1.67, 95% CI=1.02–2.73), vaginal dryness (POR=3.97, 95% CI=2.49–6.31), vaginal itching (POR=2.44, 95% CI=1.55–3.83), loss of libido (POR=3.08, 95% CI=1.92–4.94) and partnership (POR=2.22, 95% CI=1.29–3.82) remained associated with dyspareunia. Our results agree with prior studies. Additional studies of FSD in Puerto Rican women are highly warranted.